SEMANTIC ANALYSIS OF PROVERBS EXPRESSING GENDER RELATIONS IN ENGLISH, RUSSIAN AND UZBEK LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article deals with the English, Uzbek, Russian folk proverbs related to gender. The aim was to analyze the semantic analysis of the social status of the concepts of male and female. Moreover, we observed lexemes that represent family members mainly in family relations, Metaphorically expressed, and we try to compare, contrast and analyze the semantic features of Uzbek, Russian and English proverbs expressing gender relations, taken as examples from literary works. . Below we will look at the meanings and alternatives of some English and Russian proverbs in Uzbek.